Individualized implicit verbal feedback, a key tool to unlock the potential of video instruction and feedback in talented female soccer players? - Nijmeijer, E. M.; Kempe, M.; Elferink-Gemser, M. T.; Benjaminse, A. (Journal of Sports Sciences, 2026)
This study aims to examine the effects of a four-week intervention using skilled model video instruction and individualized video and implicit verbal feedback on sidestep cutting in youth female soccer players. Forty-eight talented adolescent subjects practiced and received general task instructions. The VIDEO group received skilled model video instruction during practice. The VIDEO+SELF group received video feedback of their own execution alongside skilled model video instruction. The VIDEO+SELF+VB received all components of the VIDEO+SELF group plus implicit verbal feedback. Linear mixed model analysis was performed to analyse lower extremity kinematics and kinetics, and vertical ground reaction force of baseline, immediate post, and one-week retention tests (a=0.05). Significant effects were found from baseline to retention in the VIDEO+SELF+VB group; hip flexion (p = .025, difference: +2.1°) and abduction angle (p < .001, difference: -5.3°), knee flexion (p = .014, difference: +2.5°) and adduction angle (p < .001, difference: -9.6°), and hip abduction moment (p < .001, difference: -0.96 Nm/kg) at initial contact. These increases in sagittal plane and decreases in frontal plane motion may lower ACL injury risk. On top of skilled model video instruction, the combination of individualized video feedback with implicit verbal feedback led to improvements of movement execution in female soccer players.